กระบวนการแปรรูปด้วยเอนไซม์และลักษณะเฉพาะของน้ำพุทรา Ziziyphus mauritiana Lam. เข้มข้นที่มีใยอาหารสูง - ธีระ มีโอภาสมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The optimum condition of Pectines Ultra SP-L were pH 4 and 40C - 50C. For Pectinex Ultra SP-L (1360 Unit/ml.) that used in 3 jujube groups @ 10g. found that 1. Minced jujube pulp that had particle size less than 1.5 mm. that used pectinase (30 Unit/ml.) 1 ml. and reaction time was 8 hrs. 2. Minced jujube pulp that had particle size more than 1.5 mm. that used pectinase (30 Unit/ml.) 1 ml. and reaction time was 7 hrs. 3. Minced whole jujube that used pectinase (30 Unit/ml.) 1 ml. and reaction time was 8 hrs. For minced jujube pulp that had particle size more than 1.5 mm. should to clave and mince that increased the output and claved at 121 C 15 min. could to develop the odor of concentrated jujube syrup. For the continuous process found that should to add new jujube in the process for round 1 - round 3. In the part of round 4 should to add Pectinase. The characterization of concentrated jujube syrup could divide into 4 groups were 1. Dietary Fiber found that should to add Dietary Fiber from jujube 4.06 g. in product (for 100 ml.) 2. Odor found that concentrated jujube syrup had strong odor than fresh jujube juice 3. Antioxidant found that the concentration of concentrated jujube syrup that could to inhibit free radicals 50% (EC50) was 165.806 ml. 4. Shelf life of concentrated jujube syrup that stored in the bottle found that storage at 4C for 6 weeks or storage at room temperature for 4 weeks couldn t detect yeast and mould. In the part of pilot scale for jujube juice should to add concentrated jujube syrup was 30% and then adjusted to 24 BAR was the formula that consumers accepted.